Insulin-like growth factor-1 promotes cell cycle progression via upregulation of cyclin D1 expression through the phosphatidylinositol 3-kinase/nuclear factor-κB signaling pathway in FRTL thyroid cells - Ren Meng; Zhong Xia; Ma Chun-yan; Sun Ying; Guan Qing-bo; Cui Bin; Guo Jun; Wang Hai; Gao Ling; Zhao Jia-jun (Acta Pharmacologica Sinica, 2016)
Aim: Insulin-like growth factor-1 (IGF-1) is an important hypertrophic and cell cycle progression factor for a number of cell types. It has been proven that IGF-1 is involved in the regulation of thyroid proliferation and cell cycle progression; however, the exact mechanism of this regulation has not been fully elucidated. In the present study, we investigated the effect of IGF-1 on the expression of cyclin D1, an important cell cycle regulatory protein, and a signaling pathway involved in IGF-1’s effect on cyclinD1 expression in FRTL thyroid cells. Methods: FRTL thyroid cells were treated with IGF-1 or vector control for 24 h. As appropriate to individual experiments, a phosphatidylinositol 3-kinase (PI3K) inhibitor, LY294002, and/or a nuclear factor-κB (NF-κB) inhibitor, BAY11-7082, were added 1 h prior to IGF-1 treatment. Western blotting was used to detect cyclin D1 protein expression. Immunofluorescence was performed to analyze the expression of IκBα, an NF-κB inhibitory protein. Cell cycle analysis was performed by fluorescence activated cell sorting (FACS). Results: IGF-1 increased the cyclin D1 expression in thyroid cells. This increase was blocked by pretreatment with LY294002 or BAY11-7082. Further studies showed that IGF-1 specifically induced NF-κB activity. Treatment with IGF-1 could accelerate cell cycle progression from G0/G1 to S phase, whereas this progression was inhibited by the presence of LY294002 or BAY11-7082. Conclusion: In summary, the results of the present study show that in FRTL cells, IGF-1 promotes cell cycle progression via an upregulation of cyclin D1 expression, at least partially through the PI3K/NF-κB signaling pathway.